Four Weeks of a Neuro-Meditation Program Improves Sleep Quality and Reduces Hypertension in Nursing Staff During the COVID-19 Pandemic: A Parallel Randomized Controlled Trial - Hausswirth, Christophe; Nesi, Xavier; Dubois, Alexandre; Duforez, François; Rougier, Yann; Slattery, Katie (Frontiers in Psychology, 2022)
The purpose of this study was to examine the effectiveness of a neuro-meditation program to support nurses during the COVID-19 pandemic. Forty-five (10 men and 35 women) nurses were classified into three groups based on their systolic blood pressure: normotensive (G-nor; n = 16, 43.8 ± 11.0 yr), hypertensive (G-hyp; n = 13, 45.2 ± 10.7 yr) and control (G-con; n = 16, 44.9 ± 10.6 yr). Using a parallel, randomly controlled design across a 4-week period, 10 x 30-min sessions using the Rebalance© Impulse were completed. Sleep was assessed by wrist actigraphy and subjective sleep questionnaires; perceived sleep quality, Ford Insomnia Response to Stress Test questionnaire and the Spiegel Sleep Quality questionnaire (SSQ). Blood pressure, resting heart rate, mean heart rate (HRmean), heart rate variability index (RMSSD), cortisol and alpha-amylase were also measured. Statistical analysis was completed using factorial ANOVA. Sleep improved in the G-hyp group; SSQ (P < 0.01); perceived sleep quality (P < 0.01); sleep efficiency and fragmentation index (P < 0.05). In the G-nor group, sleep was improved to a lesser extent; perceived sleep quality (P < 0.01). A significant time–group interaction was reported in resting heart rate (P < 0.01), systolic blood pressure (P < 0.01), and diastolic blood pressure (P < 0.05) with these measures being significantly reduced in the G-hyp group. RMSSD increased in the G-nor group (P < 0.01). This initial evidence suggests that neuro-meditation reduces excessive sympathetic activity, promoting enhanced sleep quality and autonomic control during periods of increased work-related stress.